2008
DOI: 10.1002/ar.20645
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric and Densitometric Changes in the Femora of Spinal Cord Transected Mice

Abstract: Spinal cord injury (SCI) leads generally to significant bone tissue loss within a few months to a few years post-trauma. Although, increasing data from rat models are available to study the underlying mechanisms of SCI-associated bone loss, little is known about the extent and rapidity of bone tissue changes in mouse models of SCI. The objectives are to characterize and describe quantitatively femoral bone tissue changes during 1 month in adult paraplegic mice. Histomorphometric and densitometric measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
3
13
1
1
Order By: Relevance
“…Bone mineral density did not change significantly, but did follow a similar trend (Figure 8). These results are similar to those found in the literature; Picard et al observed a 13.5% decrease (p<0.001) in BMC, but no significant decrease in BMD (Picard 2008). …”
Section: Representative Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Bone mineral density did not change significantly, but did follow a similar trend (Figure 8). These results are similar to those found in the literature; Picard et al observed a 13.5% decrease (p<0.001) in BMC, but no significant decrease in BMD (Picard 2008). …”
Section: Representative Resultssupporting
confidence: 92%
“…We detect a 12% loss of BMC in the femurs of mice at 40 days post-SCI using the IVIS Lumina XR. This compares favorably with a previously reported BMC loss of 13.5% by Picard and colleagues who used DXA analysis on mouse femurs post-mortem 30 days post-SCI 9 . Our results suggest that the IVIS Lumina XR provides a novel, high-resolution/high-magnification method for performing long-term, longitudinal measurements of hind limb bone density in the mouse following SCI.…”
supporting
confidence: 85%
“…16) Other reports found no change in BMD with a decline in mechanical stress. [18][19][20] In the present study, no significant differences were found in BMD between the occlusion and non-occlusion sides in either Al or Ba. This may be because measurements were taken in cortical bone 17,21) and no resorption had taken place in Al as no teeth were extracted.…”
Section: Bmdcontrasting
confidence: 75%
“…16,17 In Tx mice (N ¼ 12), histomorphometric data from our laboratory revealed a drastic decrease in trabecular bone volume (À22%, P ¼ 0.02), thickness (À11%, P ¼ 0.04) and number (À15%, P ¼ 0.09) within 10-30 days post-trauma (Table 1). 6 Densitometric measurements using dual-energy X-ray absorptiometry on the femoral bones of Tx mice (N ¼ 14) reported no change in bone mineral density but a 14% reduction (Po0.001) in bone mineral content. Other models of disuse and immobilization have also reported comparable bone losses.…”
Section: Femoral Bonesmentioning
confidence: 99%
“…[5][6][7][8] All experimental procedures were conducted in accordance with the Canadian Council for Animal Care guidelines and accepted by the Laval University Animal Care, Use and Ethics Committee. In brief, adult male CD1 mice (Charles River Canada, St Constant, Quebec) weighing 30-40 g were used.…”
Section: Animal Modelmentioning
confidence: 99%